Efficacy of Chitosan in promoting wound healing in extraction socket: A prospective study - Akshat Gupta; Vidya Rattan; Sachin Rai (Elsevier, 2019)
Purpose: Chitosan has been shown to promote wound healing and induce bone formation. The aim of this split-mouth study was to evaluate the effectiveness of chitosan based dressing in wound healing after lower third molar extraction. Method: Asymptomatic symmetrical mandibular third molars were extracted simultaneously in 27 patients and Chitosan dressing was placed into the extraction socket in the test side. Pain scores were recorded on VAS using a 0 to 10 pain score. Wound healing was compared between right and left side. Radiographic findings were evaluated by observing lamina dura and density of extraction socket. Results: Test group had more pain than control at all time intervals and unerupted tooth sites showed mean pain score significantly more than erupted tooth sites. Test group was superior to control in event of wound healing. Healing was significantly better in erupted tooth than unerupted tooth. At second week 12 sites showed better radiographic findings in chitosan treated group compared to 3 sites in the control group. At third month, 14 sites showed improved bone formation in chitosan treated group compared to 4 in control group. None of the unerupted teeth group showed better radiographic finding in test side at 2 week and 3 month compared to erupted teeth group. Conclusion: Chitosan is effective in promoting wound healing and early osteogenesis in erupted tooth socket after extraction. We recommend that chitosan dressing should be used in the sockets of erupted tooth after extraction but should be avoided in unerupted or impacted teeth cases.